Social Networking Media: Going One Step Ahead for Smoking Awareness and IEC - Bansari Chawada; A P Kadia; J K Kosambiya; S L Kantharia (Medsci Publications, 2013)
Introduction: New digital media (e.g. Internet, text messaging and social networking websites 'SNW') have dramatically altered the communication landscape, especially for youth. These communication platforms can be used as a tool for engaging youth in health promotion and risk reduction. The study has done to determine the efficacy of using social networking site as a media to deliver tobacco related health messages. Methods & Material: A webpage named "Smoke Free India" was created on Facebook and was put under 'Sponsored advertisement' for 15 days targeted on Indian population. Short messages regarding smoking and tobacco in the form of text, images, video clips and web links were shared on the page for 30 days. Results: Total 907 users from different cities "Liked" the page, out of that 63.8% were by age of 13 to 17 years. Male gender preponderance was seen for maximum likes in all age groups. Highest uptake occurred for the images followed by text update, video clips, and web links. While use of internet media is considered as challenge in tobacco control policy, the present study favours use of SNM as a communication tool to spread health messages among the internet users.